The Relationship between Segmentation and Question Location within Mobile Video Platforms for Enhancing the Ability of Recall - Zaki, Marwa (International Journal of Interactive Mobile Technologies (iJIM), 2019)
the current research aimed at identifying the relationship between segmentation of video clips (Segmented Video (SV) / Non-Segmented Video (NSV) and Question location (Pre-questions Preq / Post question Postq) through Mobile Video Platforms on affecting the Recall ability among some students of the College of Education. The semi-experimental approach was used as based on the factorial designs (2 Ã— 2). The research sample consisted of (63) female students from the College of Education at the University of Jeddah and randomly distributed to the four specified research groups. A Recall test has been developed. Analysis of variance (one and two) (ANOVA), Partial Eta Squared, and Schiff's post hoc comparison were employed to analyze data. The results showed the effectiveness of the segmented videos as compared to the non-segmented videos, and of the pre-questions as compared to the post questions, it also showed the priority of the fourth treatment of the interaction between segmented videos and pre-questions locations as compared with other experimental treatments.